2009
DOI: 10.1109/tns.2009.2013347
|View full text |Cite
|
Sign up to set email alerts
|

A Self-Checking Scheme to Mitigate Single Event Upset Effects in SRAM-Based FPAAs

Abstract: Abstract-In this work the problem of Single Event Upset (SEU) is considered in a recent analog technology: The Field Programmable Analog Arrays (FPAAs). Some FPAA models are based on SRAM memory cells to implement the user programmability, which makes this kind of device vulnerable to SEU when employed in applications susceptible to the incidence of radiation. In the former part of this work some fault injection experiments are made in order to investigate the effects of SEU in the SRAM blocks of a commercial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…In the first experiment, the circuit programmed into the FPAA was a self-checking scheme, based on redundancy, which was proposed in [3] to detect functional deviations on the circuit. Although in [3] this scheme was originally conceived to deal with bit-flips (due to SEU) in the programming memory of the device, the proposed error detection circuit is able to detect any functional deviation in the analog blocks. Moreover, this scheme presents a variety of analog functions, such as two second order filters, a subtractor and two comparators, in such a way that different analog building blocks are investigated.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the first experiment, the circuit programmed into the FPAA was a self-checking scheme, based on redundancy, which was proposed in [3] to detect functional deviations on the circuit. Although in [3] this scheme was originally conceived to deal with bit-flips (due to SEU) in the programming memory of the device, the proposed error detection circuit is able to detect any functional deviation in the analog blocks. Moreover, this scheme presents a variety of analog functions, such as two second order filters, a subtractor and two comparators, in such a way that different analog building blocks are investigated.…”
Section: Methodsmentioning
confidence: 99%
“…However, few works have been done so far concerning radiation effects in programmable analog devices. In a previous work, Manuscript the effects of bit-flips in the Static Random Access Memory (SRAM) blocks of a commercial FPAA, potentially caused by Single-Event Upset (SEU), were investigated [3]. However, experimental radiation data on FPAAs are not widely available in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Results indicate a very low aliasing probability due to single faults in the checker (0.24%) [5]. Furthermore, recent experiments showed that, with an increase of 25% of the checker area (eliminating non-duplicated paths), no aliasing occurs.…”
Section: A Single Event Upsetsmentioning
confidence: 90%
“…For this purpose, single bit inversions are injected in the FPAA programming bitstream, and the effects on the programmed design are investigated. Then, a self-checking scheme is proposed [5]. This scheme restores the original programming data if an error is detected.…”
Section: A Single Event Upsetsmentioning
confidence: 99%
“…In SRAM-based FPGAs, an error may occur, due to an SEU, when an energetic particle hits a memory cell of the device, causing a bit-flip [3]. The effects of SEU in programmable analog technologies were first investigated in [4], showing that the inversion of a single programming bit may be catastrophic to the system functionality.…”
Section: Introductionmentioning
confidence: 99%